Email Overload? Brain and Behavioral Responses to Common Messaging Alerts Are Heightened for Email Alerts and Are Associated With Job Involvement - Uther, Maria; Cleveland, Michelle; Jones, Rhiannon (Frontiers in Psychology, 2018)
We tested brain and behavioural responses to two common messaging alerts (Outlook and Android whistle) using an oddball paradigm, where participants had to detect the two alerts among a background of white noise and occasional matched, distractor stimuli. Twenty-nine participants were tested using a behavioural target detection task and a subset of fourteen were tested both with ERP and behavioural oddball detection. For the ERP recordings, participants were instructed to attend to a distractor DVD in one condition and in the other, to actively attend to the stimuli. We measured MMN and P3a components and questionnaire responses to job involvement, rumination and work-life balance. There were significantly larger MMN responses to target alert signals, but only in the ignore condition. In both ignore and attend conditions, MMN was larger for the Android stimuli, probably as a result of the larger physical discriminability for the Android tone. On the other hand, there was a significant P3a for Outlook tones, but not for Android tones in the non-attending condition. Neither alert showed significant P3a activity within the attend condition, but instead later frontal positivity, which was larger for the Outlook alert (in comparison to its matched distractor) and this effect was not seen for the Android tones. This was despite the Outlook alert being less perceptually discriminable compared to the Android alert. These findings suggest that the indices of attentional processing are more affected by the significance of the alert than the physical qualities. These effects were coupled with the finding that the faster reaction times to the Outlook sounds were correlated with greater job involvement. These data suggest that work-related messages might signal greater attentional switch and effort which in turn may feed into greater job involvement.